2006
DOI: 10.1139/x05-249
|View full text |Cite
|
Sign up to set email alerts
|

Exotic bark- and wood-boring Coleoptera in the United States: recent establishments and interceptions

Abstract: In addition, summary interception data are presented for the wood-associated beetles in the families Bostrichidae, Buprestidae, Cerambycidae, Curculionidae, Lyctidae, Platypodidae, and Scolytidae, based on the USDA Animal and Plant Health Inspection Service "Port Information Network" database for plant pests intercepted at US ports of entry from 1985 to 2000. Wood-associated insects were most often intercepted on crating, followed by dunnage and pallets. The five imported products most often associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
384
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(392 citation statements)
references
References 23 publications
3
384
1
4
Order By: Relevance
“…as the most serious and surprising problems stop resembling black swan events) significant biological and pathological traits may be revealed that illuminate some of their mysterious aspects. Interdiction via quarantine should play a prominent role in managing these problems (59). Likewise, once a problem has established in an area an enhanced awareness is needed of the risks that are posed by the movement of infested materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as the most serious and surprising problems stop resembling black swan events) significant biological and pathological traits may be revealed that illuminate some of their mysterious aspects. Interdiction via quarantine should play a prominent role in managing these problems (59). Likewise, once a problem has established in an area an enhanced awareness is needed of the risks that are posed by the movement of infested materials.…”
Section: Discussionmentioning
confidence: 99%
“…Although scolytines constitute less than 0.2% of all insect species, they have accounted for more than half of all interceptions at international ports of entry, due primarily to their association with packing materials that are made of nontreated wood (59). Beetles constituted 84% of the insects that were associated with wood materials imported into Chile and New Zealand, and 92% of the detections in the US (59).…”
Section: ) Have Extreme Impacts;mentioning
confidence: 99%
“…Despite efforts to combat this problem through improved regulatory controls in international trade, the accidental introduction of non-native forest pests in wood packaging materials such as pallets and dunnage, as well as commodities such as nursery stock, lumber, and manufactured goods, continues [4][5][6][7]. Although a relatively small proportion of these introduced species become serious invasive pests in their invaded regions, increasing numbers of forest insects and diseases are devastating natural and urban forests worldwide [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This European insect has successfully established in South America (Argentina, Brazil, Paraguay, Uruguay and Chile), North America, Australia and New Zealand (Haack 2006, Wood 2007. It is a multivoltine species with up to 4 generations per year in Chile (Ruiz and Lanfranco 2008).…”
Section: Introductionmentioning
confidence: 99%